2019
DOI: 10.1002/masy.201800163
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recovery of Metal Ion by Using Hydrogel With Different Inner pH

Abstract: New metal ion recovery method with hydrogels as a reaction and separation media has been investigated. Hydrogels based on copolymers of 2‐(Dimethylamino)ethyl methacrylate, N‐3‐(Dimethylamino)propyl acrylamide, and N,N‐dimethylacrylamide are prepared. Diethyleneglycol dimethacrylate is used as a crosslinker. The hydrogel with tertiary amino group exhibited high pH value inside of them when they swelled in water because the tertiary amino group was protonated by water and produced hydroxide ion was retained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Reacting systems in contact with a reservoir are ubiquitous in chemical research, especially in colloid and polymer science. Such a setup is widely used in applications to separate or purify substances, , for example, in biomedical or water purification. Other applications include osmotic motors or sensors . A specific example of such a system is a solution of polyelectrolytes in a dialysis bag immersed in a reservoir solution at a given pH and salinity, as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reacting systems in contact with a reservoir are ubiquitous in chemical research, especially in colloid and polymer science. Such a setup is widely used in applications to separate or purify substances, , for example, in biomedical or water purification. Other applications include osmotic motors or sensors . A specific example of such a system is a solution of polyelectrolytes in a dialysis bag immersed in a reservoir solution at a given pH and salinity, as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…The partitioning of salt ions and H + ions affects the swelling of polyelectrolyte hydrogel and is coupled to the ionization degree of the polyelectrolyte. The ionization degree determines the gel’s ability to capture or release ions at various pH values, which is relevant in desalination, controlled release, and water treatment applications. , Semipermeable membranes are not necessary for such systems because gel connectivity prevents the polymer from escaping the gel phase without affecting its ability to exchange ions with the surrounding reservoir solution. Similarly to gels, partitioning of salt ions affects the stability of phase-separated complex coacervates. , The envisioned application of coacervates to the separation of charged proteins requires understanding the partitioning between the coacervate and the supernatant solution, while protein release by a change in pH depends on the acid–base ionization equilibrium in the coacervate, which is inherently coupled to the partitioning of H + ions.…”
Section: Introductionmentioning
confidence: 99%
“…36 Cunha et al reported that CaP formation is favored in granules with an increased internal pH from biological activity. 37 In hydrogel systems, increased internal pH values have been engineered for the removal of heavy metal ions through selection of appropriate monomer units 38 or for the protection of pH-sensitive enzymes through the inclusion of brucite. 39 These engineered hydrogels were respectively applied to selectively recover metal ions and protect acid-sensitive compounds.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…aects the swelling of polyelectrolyte hydrogels and is coupled to the ionization degree of the polyelectrolyte. The ionization degree determines their ability to capture or release ions at various pH values, which is relevant in desalination, controlled release and water treatment applications 9,10 . Semipermeable membranes are not necessary for such systems because gel connectivity prevents the polymer from escaping the gel phase without aecting its ability to exchange ions with the surrounding reservoir solution.…”
Section: Introductionmentioning
confidence: 99%